The interaction between teaching competencies and self-efficacy in fostering engagement amongst distance learners: A path analysis approach - Baba Rahim, Norizan (Universiti Utara Malaysia Press, 2022)
Purpose - Distance learners are expected to actively participate in online learning settings to improve their cognitive level and promote more meaningful learning. However, without specific teaching skills and competencies from the instructors together with belief and capability of the distance learners themselves, their engagement in online learning would not be achieved. Limited studies have examined the extent of self-efficacy in encouraging student engagement in learning, especially within online learning settings. Thus, this study examined self-efficacy as a moderator to test its influence on the relationship between online teaching competencies and student engagement.